High-toughness carbon-glass super-hybrid composite material as well as preparation method and application thereof

By using super-mixed fusion wire and vacuum-assisted resin transfer molding process in carbon glass composites, a high-tough carbon glass ultra-mixed composite material was prepared, which solved the problems of poor design, low degree of mixing and poor toughening effect of existing interlayer mixed materials, and achieved higher mechanical properties and toughness.

CN119526645AActive Publication Date: 2025-02-28ZHENGZHOU UNIV +1

Patent Information

Application Number
CN202411790716.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing mixed composite materials between carbon glass layers have problems such as poor designability, low degree of carbon glass mixing, and poor toughening effect.

Method used

The carbon fiber widening wire and glass fiber widening wire obtained by preparing ultra-thin carbon fiber fiber spreading equipment are super mixed and combined with vacuum-assisted resin transfer molding process to prepare carbon glass ultra-hybrid composite materials with different carbon glass volume ratios and different degree of mixed degrees.

Benefits of technology

It achieves better toughening effect, improves the tensile modulus, elongation of break, bending limit strain, loss factor and energy absorption of composite materials, which is better than traditional interlayer mixed composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119526645A_ABST
    Figure CN119526645A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness carbon-glass super-hybrid composite material as well as a preparation method and application thereof. Carbon fiber broadened filaments and glass fiber broadened filaments prepared by ultrathin carbon fiber spreading equipment are subjected to super-hybrid doubling, and the carbon-glass super-hybrid composite material with better reinforcing and toughening effects is prepared through a vacuum-assisted resin transfer molding process. An existing mixing method is improved, the problems that an interlayer mixing method is poor in mixing designability, low in fiber mixing degree, poor in toughening effect and the like are solved, the prepared carbon-glass super-mixed composite material has better reinforcing and toughening effects, and under the same carbon-glass volume ratio, the carbon-glass super-mixed composite material has the better reinforcing and toughening effects. The carbon-glass super-hybrid composite material is higher in tensile modulus, elongation at break and loss factor, and a drop hammer impact test shows that the carbon-glass super-hybrid composite material has the characteristics of larger energy absorption, small damage area and the like. In conclusion, the carbon-glass super-hybrid composite material shows better reinforcing and toughening effects, the mechanical property of the composite material is improved, and the carbon-glass super-hybrid composite material is better than an interlayer hybrid composite material on the whole.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation and performance of a high-toughness carbon-glass super-hybrid composite material, in particular to its application in an inner panel frame of an automobile door. Background Art

[0002] The inner door panel frame of the car (such as Figure 1 As shown in the figure, high-strength steel, aluminum alloy or composite materials are mainly used. As the secondary load-bearing part of the vehicle, the inner door panel frame of the car bears a certain supporting role and protects the vehicle from various forces during driving. The properties of the selected materials play a decisive role in the safety performance and overall strength of the car. At present, high-strength steel, aluminum alloy and composite materials are the first choice of automobile manufacturers because they not only have excellent strength and rigidity, but also show good corrosion resistance.

[0003] During the production process, manufacturers will accurately select the right material based on the characteristics of the vehicle model and the target market, such as sedans, SUVs or trucks, as well as the vehicle's use environment and cost budget. The choice of automotive frame material will also affect the weight of the vehicle, which in turn affects fuel economy. Therefore, choosing the right automotive door inner panel frame material is crucial to improving vehicle performance and economic efficiency. This is not only related to the driver's safety, but also to the cost in use.

[0004] In the context of the country's advocacy of energy conservation and emission reduction, carbon fiber composite materials have been widely used in many fields due to their light weight and high strength, and have gradually begun to replace some metal materials. Especially in the fields of automobiles, high-end sports goods, and aerospace, carbon fiber composite materials play an increasingly important role. However, the high cost and low toughness of carbon fiber composite materials are two aspects that limit their wider application. In response to these two problems, the fiber blending method is currently mainly used for optimization. The more common method is to use low-cost, high-toughness polymer fiber materials or other fibers to mix with carbon fibers to prepare hybrid fiber composite materials, so as to reduce costs and enhance toughness.

[0005] Glass fiber has the advantages of low cost and high toughness, and has become the mainstream fiber material mixed with carbon fiber. At present, the main way of mixing is interlayer mixing, that is, mixing by alternating layers of carbon fiber woven cloth and glass fiber woven cloth (carbon-glass interlayer mixing). Because the woven cloth is usually thicker, there are problems such as poor designability and low mixing degree of carbon fiber and glass fiber, which leads to the inability to give full play to the advantages of the two fibers. In view of this, the present invention provides a high-toughness carbon-glass super-hybrid composite material used in the door inner panel frame. Summary of the invention

[0006] In view of the problems of low designability, low carbon-glass interlayer hybrid composite materials, poor toughening effect, etc., the present invention provides a high-toughness carbon-glass super-hybrid composite material and a preparation method thereof, wherein the carbon fiber widening yarn and the glass fiber widening yarn prepared by the ultra-thin carbon fiber spreading device are super-hybrid and wired, and a carbon-glass super-hybrid composite material with better strengthening and toughening effect is prepared by a vacuum-assisted resin transfer molding process. The present invention prepares composite materials with different carbon-glass volume ratios, different mixing degrees and better strengthening and toughening effect, and applies them to the door inner panel frame.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A method for preparing a high-toughness carbon-glass super-hybrid composite material comprises the following steps:

[0009] (1) Preparation of carbon-glass super-hybrid braids

[0010] (a) Preparation of super hybrid fiber widening yarn: carbon fiber widening yarn (i.e., 12K T700 carbon fiber tow widened to 24 mm, 1.4 times the width of conventional mechanical widening, and its thickness is only 0.02 mm, 60% lower than the thickness of conventional mechanical widening) and glass fiber widening yarn (i.e., 20K T300 glass fiber tow widened to 15 mm, 1.5 times the width of conventional mechanical widening, and its thickness is only 0.03 mm, 40% lower than the thickness of conventional mechanical widening) obtained by air flow disturbance type carbon fiber widening equipment (ZL202111589981.4) are mixed according to different carbon-glass volume ratios, and the fiber filaments are paralleled by upper and lower parallel rollers, and then the fiber filaments are paralleled as a whole by other rollers to obtain super hybrid fiber widening yarn;

[0011] (b) Preparing a braid: The super hybrid fiber widening yarn is braided into a carbon-glass super hybrid braid with a thickness between 0.04 mm and 0.08 mm by a braiding device.

[0012] (2) Preparation of carbon-glass superhybrid composites

[0013] (A) Layer design: Since two types of fibers have been super-mixed in the super-hybrid fiber braid, the super-hybrid fiber braids are directly layered, and the optimal thickness range of the super-hybrid fiber braid after layering is 1.0-1.4 mm;

[0014] (B) Vacuum assisted resin transfer molding: The super hybrid fiber braid after layering is placed on a smooth stainless steel template, and the fiber braid is completely infiltrated with epoxy resin glue, sealed, and cured to obtain a carbon-glass super hybrid composite material with a thickness between 2.6 mm and 2.8 mm.

[0015] Furthermore, the carbon fiber stretched yarn and the glass fiber stretched yarn after the overall paralleling in step (a) penetrate and cross each other in the thickness direction and further stretch due to the existence of tension, thereby obtaining a wider stretch.

[0016] Furthermore, in the step (a), the volume ratios of the carbon fiber stretch yarns and the glass fiber stretch yarns are 2:1, 1:1, and 1:2, respectively.

[0017] Furthermore, when the volume ratio of the carbon fiber stretched yarn to the glass fiber stretched yarn was 2:1, 1:1, and 1:2, SCGC carbon-glass super-hybrid braid, SCG carbon-glass super-hybrid braid, and SGCG carbon-glass super-hybrid braid were prepared, respectively.

[0018] In the step (A), 10 layers of SCGC fiber braids, 15 layers of SCG fiber braids, and 10 layers of SGCG fiber braids are laid flat, respectively, to prepare super hybrid ply structures with carbon-glass volume ratios of 2:1 (SCGC), 1:1 (SCG), and 1:2 (SGCG), respectively.

[0019] The specific preparation method of the carbon-glass super-hybrid composite material in step (B) is as follows: the super-hybrid fiber braid after layering is placed on a smooth stainless steel template coated with a release agent and an anti-adhesive film, and a release cloth, a guide net, a glue-absorbing cotton, a threaded tube and a vacuum bag are placed on the braid in sequence, and 3M sealant is used to stick them around; the exhaust pipe and the glue inlet pipe are connected to the threaded pipe and fixed, the exhaust pipe is connected in series with the buffer kettle and the vacuum pump, the glue inlet is locked, and the vacuum pump is turned on for vacuuming. When the vacuum pump pressure reaches one atmosphere, check Check for air leakage. After making sure that the whole device is not leaking, connect the glue inlet pipe to the beaker containing degassed epoxy resin glue. Then open the glue inlet, and the epoxy resin glue enters the sealed mold cavity under the action of the vacuum pump. After the epoxy resin glue completely infiltrates the fiber braid, seal the glue inlet and the air exhaust port, cure at room temperature for 24 hours, and then place in an oven and post-cure at 60°C for 2 hours. After taking out, remove the hybrid composite material from the mold, remove the demoulding cloth, guide net, and vacuum bag to obtain a carbon-glass super-hybrid composite material.

[0020] Furthermore, the preparation method of epoxy resin glue is as follows: epoxy resin and curing agent are mixed in a mass ratio of 3:1 and stirred evenly. The mixed epoxy resin contains a large number of bubbles. At this time, the epoxy resin needs to be placed in a vacuum drying oven to vent for 10-12 minutes. After venting, the epoxy resin is transparent, and the interior is clear and uniform without bubbles.

[0021] The invention also provides a high-toughness carbon-glass super-hybrid composite material prepared by the preparation method.

[0022] The application of the high-toughness carbon-glass super-hybrid composite material described in the present invention on the inner panel frame of an automobile door, compared with the interlayer hybrid composite material, the super-hybrid composite material with three carbon-glass volume ratios has a maximum tensile modulus of 55 MPa, an increase of 19.5%; the maximum elongation at break is 1.9%, an increase of 10.4%; the maximum bending limit strain is 2.66%, an increase of 39.2%; the maximum loss factor is 0.595, an increase of 6.63%; the minimum damage area after the impact test is 4.2%, a decrease of 14.2%; the maximum absorbed energy is 24.8 J, an increase of 4.6%.

[0023] The beneficial effects of the present invention are as follows: the existing hybrid method is improved, and the problems of poor hybrid design, low fiber mixing degree and poor toughening effect of the interlayer hybrid method are solved. The obtained carbon-glass super hybrid composite material presents a better strengthening and toughening effect, which is specifically reflected in that: under the same carbon-glass volume ratio, the carbon-glass super hybrid composite material has higher tensile modulus, elongation at break and loss factor, and the drop hammer impact test shows that the absorption energy is larger and the damage area is small. The application of the high-toughness carbon-glass super hybrid composite material of the present invention on the inner panel skeleton of the automobile door is that compared with the interlayer hybrid composite material, the tensile modulus of the super hybrid composite materials with three carbon-glass volume ratios is up to 55MPa, which is increased by 19.5%; the elongation at break is up to 1.9%, which is increased by 10.4%; the bending limit strain is up to 2.66%, which is increased by 39.2%; the loss factor is up to 0.595, which is increased by 6.63%; the damage area after the impact test is at least 4.2%, which is reduced by 14.2%; the absorption energy is up to 24.8J, which is increased by 4.6%.

[0024] In summary, the carbon-glass super-hybrid composite material exhibits better reinforcement and toughening effects, improves the mechanical properties of the composite material, and is overall superior to the interlayer hybrid composite material, becoming an excellent substitute for it. The high-toughness carbon-glass super-hybrid composite material of the present invention can be applied to the inner panel frame of a car door to exhibit excellent strength and toughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 This is a schematic diagram of the structure of the inner panel of a car door.

[0027] Figure 2 The preparation process of widened super hybrid fibers with three different carbon-glass volume ratios.

[0028] Figure 3 Design of super hybrid woven fabric plies: (a) SCGC, (b) SCG, and (c) SGCG.

[0029] Figure 4 Design for interlayer hybrid woven fabric layup: (a) LCGC, (b) LCG, (c) LGCG.

[0030] Figure 5 Flow chart for the preparation of superhybrid composites.

[0031] Figure 6 It is the tensile modulus of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0032] Figure 7 Elongation at break of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0033] Figure 8 Bending limit strain of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0034] Fig. 9 Loss factors of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0035] Fig.10 Impact test energy absorption data of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0036] Fig.11 Damage ratios of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0037] Fig.12 Storage modulus of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3.

[0038] Fig.13 Ultrasonic nondestructive testing results of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3: (a) SCGC, (b) SCG, (c) SGCG, (d) LCGC, (e) LCG, (f) LGCG.

[0039] Fig.14 Schematic diagram of vacuum-assisted resin transfer molding. DETAILED DESCRIPTION

[0040] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The carbon fiber widening yarn and glass fiber widening yarn used in the present invention are both prepared by an airflow disturbance type carbon fiber widening equipment (authorized patent: ZL202111589981.4). The carbon fiber widening yarn is a 12K T700 carbon fiber bundle widened to 24mm, which is 1.4 times the width of traditional mechanical widening, and its thickness is only 0.02mm, which is 60% lower than the traditional mechanical widening thickness; the glass fiber widening yarn is a 20K T300 glass fiber bundle widened to 15mm, which is 1.5 times the width of traditional mechanical widening, and its thickness is only 0.03mm, which is 40% lower than the traditional mechanical widening thickness.

[0042] The carbon fiber widening yarn and the glass fiber widening yarn obtained by the air flow disturbance type carbon fiber widening equipment (ZL202111589981.4) are used to prepare the carbon-glass super hybrid fiber widening yarn. Figure 2 As shown in Table 1, the preparation process of three super hybrid fiber widening yarns with different carbon glass volume ratios is shown. Examples 1-3 are three super hybrid composite materials SCGC, SCG, SGCG, and Comparative Examples 1-3 are three interlayer hybrid composite materials LCGC, LCG, LGCG, as shown in Table 1.

[0043] Table 1 Hybrid composite materials

[0044]

[0045] Example 1

[0046] The preparation method of the high-toughness carbon-glass super-hybrid composite material of this embodiment is as follows:

[0047] (1) Preparation of super hybrid widened yarns: Using air flow disturbance type carbon fiber widening equipment (authorized patent: ZL202111589981.4) to prepare carbon fiber widened yarns (i.e., 12K T700 carbon fiber tows are widened to 24 mm, which is 1.4 times the width of traditional mechanical widening, and its thickness is only 0.02 mm, which is 60% lower than the thickness of traditional mechanical widening) and glass fiber widened yarns (i.e., 20K T300 glass fiber tows are widened to 15 mm, which is 1.5 times the width of traditional mechanical widening, and its thickness is only 0.03 mm, which is 40% lower than the thickness of traditional mechanical widening), and then carbon-glass super hybrid fiber widened yarns are prepared, such as Figure 2 Shown is the preparation process of widened super hybrid fibers with three different carbon-glass volume ratios.

[0048] exist Figure 2In (a), ① and ② are carbon fiber stretched yarns and glass fiber stretched yarns, respectively, prepared by the mechanical vibration-air flow disturbance collaborative stretching method. Three upper and lower parallel rollers are used to combine ①②①, and then the whole yarn is combined by a fourth roller. After the combination, the carbon fiber stretched yarn and the glass fiber stretched yarn penetrate and cross each other in the thickness direction due to the existence of tension and are further widened, obtaining ③ with more uniform carbon-glass mixing, that is, super hybrid stretched yarn (SCGC) with a carbon-glass volume ratio of 2:1.

[0049] (2) Preparation of braided fabric: The super hybrid expanded yarn (SCGC) is braided by a braiding device to prepare a super hybrid fiber braid (SCGC) with a thickness between 0.04 mm and 0.08 mm.

[0050] (3) Layer design: Because the two fibers have been super-mixed in the super-hybrid fiber braid, the super-hybrid fiber braid (SCGC) is directly layered, and the optimal range of the total layer thickness is 1.0-1.4 mm. Among them, by laying 10 layers of SCGC fiber braid flat, a super-hybrid layer structure with a carbon-glass volume ratio of 2:1 (SCGC) can be prepared;

[0051] (4) Vacuum-assisted resin transfer molding: First, mix the epoxy resin and curing agent in a mass ratio of 3:1 and stir evenly. The mixed epoxy resin contains a large number of bubbles. At this time, the epoxy resin needs to be placed in a vacuum drying oven to exhaust for about ten minutes. After exhausting, the epoxy resin is transparent, clear and uniform inside without bubbles.

[0052] Place the fiber braid after layering on a smooth stainless steel template coated with a release agent and anti-adhesive film, place a release cloth, a guide net, a glue-absorbing cotton, a threaded tube and a vacuum bag on top of the braid in sequence, and use 3M sealant to stick around; connect the vacuum pipe and the glue inlet pipe to the threaded pipe and fix them, connect the vacuum pipe with the buffer kettle and the vacuum pump in series, lock the glue inlet, and turn on the vacuum pump to evacuate. When the vacuum pump pressure reaches one atmosphere, check for leaks. After confirming that the entire device is leak-free, connect the glue inlet pipe to the beaker, which contains epoxy resin glue, and then open the glue inlet. The epoxy resin glue enters the sealed mold cavity under the action of the vacuum pump. After the epoxy resin glue completely infiltrates the fiber braid, seal the glue inlet and the vacuum port, and cure at room temperature for 24 hours. Then, the mold was placed in an oven and post-cured at 60°C for two hours. After being taken out, the hybrid composite material was removed from the mold, and the release cloth, guide net, and vacuum bag were removed to obtain carbon-glass hybrid composite materials with different volume ratios and a thickness between 2.6mm and 2.8mm.

[0053] When the carbon-glass volume ratio is 2:1 (SCGC), the carbon fiber volume fraction is 66%. The super hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 2.

[0054] Table 2 Test data of carbon-glass ratio 2:1 super hybrid composite material

[0055]

[0056] Example 2

[0057] The preparation method of the high-toughness carbon-glass super-hybrid composite material of this embodiment is as follows:

[0058] (1) Preparation of super hybrid widened yarn: Carbon fiber widened yarn and glass fiber widened yarn are used (authorized patent: an air flow disturbance type carbon fiber widening device, ZL 202111589981.4) to prepare carbon-glass super hybrid fiber widened yarn, such as Figure 2 Shown is the preparation process of widened super hybrid fibers with three different carbon-glass volume ratios.

[0059] exist Figure 2 In (b), two parallel rollers are used to parallelize ① and ②, and then pass through a third roller. Due to the existence of tension, the carbon fiber stretched yarn and the glass fiber stretched yarn after paralleling penetrate and cross each other in the thickness direction and continue to widen, obtaining a more uniform carbon-glass mixed ④, that is, a super hybrid stretched yarn (SCG) with a carbon-glass volume ratio of 1:1.

[0060] (2) Preparing a braided fabric: The super hybrid spread yarn (SCG) is braided by a braiding device to prepare a super hybrid fiber braid (SCG) with a thickness between 0.04 mm and 0.08 mm.

[0061] (3) Layer design: The super hybrid fiber braid (SCG) is directly layered, and the total layer thickness is the same as that in Example 1 (between 1.0 and 1.4 mm). Among them, 15 layers of SCG fiber braid are laid flat to prepare a super hybrid layer structure with a carbon-glass volume ratio of 1:1 (SCG).

[0062] (4) Vacuum assisted resin transfer molding: same as Example 1.

[0063] When the carbon-glass volume ratio is 1:1 (SCG), the carbon fiber volume fraction is 50%. The super hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 3.

[0064] Table 3 Test data of carbon-glass ratio 1:1 super hybrid composite material

[0065]

[0066] Example 3

[0067] The preparation method of the high-toughness carbon-glass super-hybrid composite material of this embodiment is as follows:

[0068] (1) Preparation of super hybrid stretched yarn: Carbon fiber stretched yarn and glass fiber stretched yarn (authorized patent: an air flow disturbance type carbon fiber stretching device, ZL202111589981.4) are used to prepare carbon-glass super hybrid fiber stretched yarn, such as Figure 2 Shown is the preparation process of widened super hybrid fibers with three different carbon-glass volume ratios.

[0069] exist Figure 2 In (c), three parallel rollers are used to parallelize ②①②, and then pass through the fourth roller. Due to the existence of tension, the carbon fiber stretched yarn and the glass fiber stretched yarn after paralleling penetrate and cross each other in the thickness direction and continue to widen, obtaining a more uniform carbon-glass mixed ⑤, that is, a super hybrid stretched yarn (SGCG) with a carbon-glass volume ratio of 1:2.

[0070] (2) Preparation of braided fabric: The super hybrid expanded yarn (SGCG) is braided by a braiding device to prepare a super hybrid fiber braid (SGCG) with a thickness between 0.04 mm and 0.08 mm.

[0071] (3) Layer design: The super hybrid fiber braid (SGCG) is directly layered, and the total layer thickness is the same as that in Example 1 (between 1.0 and 1.4 mm). Among them, 10 layers of SGCG fiber braid are laid flat to prepare a super hybrid layer structure with a carbon-glass volume ratio of 1:2 (SGCG);

[0072] (4) Vacuum assisted resin transfer molding: same as Example 1.

[0073] When the carbon-glass volume ratio is 1:2 (SGCG), the carbon fiber volume fraction is 33%. The super hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 4.

[0074] Table 4 Test data of carbon-glass ratio 1:2 super hybrid composite material

[0075]

[0076]

[0077] Comparative Example 1

[0078] The preparation method of the interlayer hybrid composite material (carbon-glass volume ratio of 2:1) of this comparative example is as follows:

[0079] (1) Preparation of single fiber woven cloth: Carbon fiber stretched yarn and glass fiber stretched yarn (here, as in the embodiment, stretched by using authorized equipment) are woven into carbon fiber woven cloth and glass fiber woven cloth respectively.

[0080] (2) Layer design: In order to compare with the super hybrid woven fabric layer structure, Figure 4 In the embodiment, the interlayer hybrid ply design of the carbon fiber woven cloth and the glass fiber woven cloth is performed according to the same carbon-glass volume ratio as the super hybrid ply with a carbon-glass volume ratio of 2:1, and the total ply thickness is the same as that in Example 1 (between 1.0 and 1.40 mm). When the carbon-glass volume ratio is 2:1 (LCGC), the plies are alternately laid in the manner of C3G3C6G3C6G3C6G3C3 (C represents carbon fiber woven cloth, G represents glass fiber woven cloth, and subscripts 3 and 6 represent the number of woven cloth layers), with a total of 36 layers (each layer is about 0.03 mm), and an interlayer hybrid ply structure with a carbon-glass volume ratio of 2:1 (LCGC) can be prepared.

[0081] (3) Vacuum assisted resin transfer molding: same as step (4) of Example 1.

[0082] When the carbon-glass volume ratio is 2:1 (LCGC), the carbon fiber volume fraction is 66%. The interlayer hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 5.

[0083] Table 5 Test data of carbon-glass ratio 2:1 interlayer hybrid composite materials

[0084]

[0085] Comparison of super hybrid and interlayer hybrid under the same carbon-glass ratio (i.e. carbon-glass volume ratio is 2:1, comparison of Table 2 and Table 5) shows that in the tensile test, the tensile modulus of the super hybrid composite (Table 2) is 19.5% higher than that of the interlayer hybrid composite, and the elongation at break of the super hybrid composite is 1.3% higher than that of the interlayer hybrid composite. In the bending test, the bending limit strain of the super hybrid composite is 12.3% higher than that of the interlayer hybrid composite. In the DMA performance test, the loss factor of the super hybrid composite is 8.47% higher than that of the interlayer hybrid composite. In the drop hammer impact test, the super hybrid composite absorbs 3.8% more energy than the interlayer hybrid composite. In the ultrasonic nondestructive testing, the damage area of ​​the super hybrid composite is 10.8% less than that of the interlayer hybrid composite.

[0086] Comparative Example 2

[0087] The preparation method of the interlayer hybrid composite material (carbon-glass volume ratio of 1:1) of this comparative example is as follows:

[0088] (1) Preparation of single fiber woven fabric: Weaving carbon fiber stretched yarns and glass fiber stretched yarns into carbon fiber woven fabric and glass fiber woven fabric respectively.

[0089] (2) Layer design: In order to compare with the super hybrid woven fabric layer structure, Figure 4 In the embodiment, the interlayer hybrid ply design of carbon fiber and glass fiber woven fabric is performed according to the same carbon-glass volume ratio as the super hybrid ply with a carbon-glass volume ratio of 1:1, and the total ply thickness is the same as that of Example 2 (between 1.0 and 1.4 mm). When the carbon-glass volume ratio is 1:1 (LCG), the ply is alternately laid in the manner of C3G6C6G6C6G6C3, with a total of 36 layers (each layer is about 0.03 mm), and an interlayer hybrid ply structure with a carbon-glass volume ratio of 1:1 (LCG) can be prepared.

[0090] (3) Vacuum assisted resin transfer molding: same as step (4) of Example 1.

[0091] When the carbon-glass volume ratio is 1:1 (LCG), the carbon fiber volume fraction is 50%. The interlayer hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 6.

[0092] Table 6 Test data of carbon-glass ratio 1:1 interlayer hybrid composite materials

[0093]

[0094]

[0095] Comparison of super hybrid and interlayer hybrid under the same carbon-glass ratio (i.e. carbon-glass volume ratio is 1:1, comparison of Table 3 and Table 6) shows that in the tensile test, the tensile modulus of the super hybrid composite (Table 3) is 22.7% higher than that of the interlayer hybrid composite, and the elongation at break of the super hybrid composite is 5.5% higher than that of the interlayer hybrid composite. In the bending test, the bending limit strain of the super hybrid composite is 26.3% higher than that of the interlayer hybrid composite. In the DMA performance test, the loss factor of the super hybrid composite is 7.33% higher than that of the interlayer hybrid composite. In the drop hammer impact test, the super hybrid composite absorbs 1.9% more energy than the interlayer hybrid composite. In the ultrasonic nondestructive testing, the damage area of ​​the super hybrid composite is 6.3% less than that of the interlayer hybrid composite.

[0096] Comparative Example 3

[0097] The preparation method of the interlayer hybrid composite material (carbon-glass volume ratio 1:2) of this comparative example is as follows:

[0098] (1) Preparation of single fiber woven fabric: Weaving carbon fiber stretched yarns and glass fiber stretched yarns into carbon fiber woven fabric and glass fiber woven fabric respectively.

[0099] (2) Layer design: In order to compare with the super hybrid woven fabric layer structure, Figure 4 In the embodiment, the interlayer hybrid ply design of carbon fiber and glass fiber woven fabric is performed according to the same carbon-glass volume ratio as the super hybrid ply with a carbon-glass volume ratio of 1:2, and the total ply thickness is the same as that of Example 3 (between 1.0 and 1.4 mm). When the carbon-glass volume ratio is 1:2 (LGCG), the ply is alternately laid in the manner of C3G6C2G6C2G6C2G6C3, with a total of 36 layers (each layer is about 0.03 mm), and an interlayer hybrid ply structure with a carbon-glass volume ratio of 1:2 (LGCG) can be prepared.

[0100] (3) Vacuum assisted resin transfer molding: same as step (4) of Example 1.

[0101] When the carbon-glass volume ratio is 1:2 (LGCG), the carbon fiber volume fraction is 33%. The interlayer hybrid composite material is subjected to tensile test, bending test, DMA performance test, drop hammer impact test, and ultrasonic nondestructive testing. The specific data are shown in Table 7.

[0102] Table 7 Test data of carbon-glass ratio 1:2 interlayer hybrid composite materials

[0103]

[0104] Comparison of super hybrid and interlayer hybrid under the same carbon-glass ratio (i.e. carbon-glass volume ratio is 1:2, comparison of Table 4 and Table 7) shows that in the tensile test, the tensile modulus of the super hybrid composite (Table 4) is 11% higher than that of the interlayer hybrid composite, and the elongation at break of the super hybrid composite is 10.4% higher than that of the interlayer hybrid composite. In the bending test, the bending limit strain of the super hybrid composite is 39.2% higher than that of the interlayer hybrid composite. In the DMA performance test, the loss factor of the super hybrid composite is 6.63% higher than that of the interlayer hybrid composite. In the drop hammer impact test, the super hybrid composite absorbs 4.6% more energy than the interlayer hybrid composite. In the ultrasonic nondestructive testing, the damage area of ​​the super hybrid composite is 14.2% less than that of the interlayer hybrid composite.

[0105] In summary, the three embodiments and comparative examples are comprehensively compared as follows (specific data such as Figure 6-13 , as shown in Table 8):

[0106] Table 8 Energy absorbed by composite materials

[0107]

[0108] (1) In terms of tensile modulus, when the carbon-glass volume ratio is 2:1, 1:1 and 1:2, the tensile modulus of the super hybrid composite is increased by 19.5%, 22.7% and 11% respectively compared with the interlayer hybrid composite. It can be seen that the tensile modulus of the super hybrid composite is significantly better than that of the interlayer hybrid composite, and it has a better reinforcement effect.

[0109] (2) In terms of elongation at break, when the carbon-glass volume ratios were 2:1, 1:1 and 1:2, the elongation at break of the super-hybrid was 1.3%, 5.5% and 10.4% higher than that of the interlayer hybrid, respectively. It can be seen that the elongation at break of the super-hybrid composite material is higher than that of the interlayer hybrid composite material, and the improvement effect is more obvious when the carbon fiber content is lower, indicating that the more uniform carbon-glass mixing effect of the super-hybrid fiber composite material enables the carbon fiber and glass fiber to better play a synergistic role, thereby producing a strengthening and toughening effect.

[0110] (3) In terms of bending limit strain, when the carbon-glass volume ratio is 2:1, 1:1 and 1:2, the bending limit strain of the super hybrid composite is 12.3%, 26.3% and 39.2% higher than that of the interlayer hybrid composite. It can be seen that the bending limit strain of the super hybrid composite is significantly higher than that of the interlayer hybrid, indicating that the super hybrid composite has a better toughening effect under bending load.

[0111] (4) In terms of the loss factor results of the DMA performance test, when the carbon-glass volume ratio is 2:1, 1:1 and 1:2, the loss factor of the super-hybrid fiber composite is higher than that of the interlayer hybrid composite, indicating that the super-hybrid fiber composite has greater damping. In the super-hybrid composite, the mixing of carbon fiber and glass fiber is more uniform than that of the interlayer hybrid composite. The carbon fiber reinforcement and glass fiber toughening work together, resulting in greater damping and dissipating more energy in deformation, thus showing a better energy absorption effect.

[0112] (5) In the drop hammer impact test, when the carbon-glass volume ratio was 2:1, 1:1 and 1:2, the energy absorbed by the super-hybrid composite was 3.8%, 1.9% and 4.6% higher than that of the interlayer hybrid composite, respectively. The absorbed energy of the super-hybrid material was higher than that of the interlayer hybrid composite, indicating that the fiber dispersion in the super-hybrid composite was more uniform, showing a better energy absorption effect.

[0113] (6) In terms of damage area ratio, when the carbon-glass volume ratio is 2:1, 1:1 and 1:2, the damage area of ​​the super-hybrid composite material is reduced by 10.8%, 6.3% and 14.2% respectively compared with the interlaminar hybrid composite material, indicating that the super-hybrid material has better impact resistance.

[0114] The above results indicate that the super hybrid composite material prepared by the present invention overcomes the defects of poor interlayer mixing design, low fiber mixing degree and poor toughening effect, and achieves more uniform mixing within the carbon fiber and glass fiber bundles, so that the two can better cooperate with each other and give play to their own advantages, showing better reinforcement and toughening effects and improving the mechanical properties of the composite material.

[0115] The basic principles and main features of the present invention as well as the advantages of the present invention are shown and described above.

[0116] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a high-toughness carbon-glass super-hybrid composite material, characterized in that The following steps are involved: (1) Preparation of carbon-glass super-hybrid braids; (2) Preparation of carbon-glass superhybrid composites.

2. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 1, characterized in that: The step (1) of preparing the carbon-glass super hybrid braid comprises the following steps: (a) preparing super hybrid fiber widening yarn: mixing the carbon fiber widening yarn and the glass fiber widening yarn obtained by using the air flow disturbance type carbon fiber widening equipment according to different carbon-glass volume ratios, using upper and lower parallel rollers to spool the fiber yarns, and then passing other rollers to spool the fiber yarns as a whole to obtain the super hybrid fiber widening yarn; (b) Preparation of braided fabric: The super hybrid fiber expanded yarn is braided into a carbon-glass super hybrid braid using a braiding device.

3. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 2, characterized in that: In the step (a), the volume ratios of the carbon fiber stretched yarns and the glass fiber stretched yarns are 2:1, 1:1, and 1:2, respectively.

4. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 2, characterized in that: When the volume ratio of the carbon fiber stretched yarn to the glass fiber stretched yarn is 2:1, 1:1, and 1:2, SCGC carbon-glass super-hybrid braid, SCG carbon-glass super-hybrid braid, and SGCG carbon-glass super-hybrid braid are prepared respectively.

5. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 2, characterized in that: In step (a), the carbon fiber stretched yarn and the glass fiber stretched yarn after the overall yarn drawing are mutually interpenetrated and crossed in the thickness direction and further stretched due to the existence of tension, thereby obtaining a wider stretch.

6. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 1, characterized in that: The step (2) of preparing the carbon-glass super hybrid composite material comprises the following steps: (A) Layer design: Because the two types of fibers have been super-mixed in the super-hybrid fiber braid, the super-hybrid fiber braids are directly layered separately, and the thickness of the super-hybrid fiber braid after layering is 1.0-1.4 mm; (B) Vacuum assisted resin transfer molding: The super hybrid fiber braid after layering is placed on a smooth stainless steel template, and the fiber braid is completely infiltrated with epoxy resin glue, sealed, and cured to obtain a carbon-glass super hybrid composite material.

7. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 6, characterized in that: Step (B) The specific preparation method of the carbon-glass super hybrid composite material is as follows: the super hybrid fiber braid after layering is placed on a smooth stainless steel template coated with a release agent and an anti-adhesive film, and a release cloth, a guide net, a glue-absorbing cotton, a threaded tube and a vacuum bag are placed on the braid in sequence. M sealant is pasted around; an exhaust pipe and a glue inlet pipe are connected to the threaded pipe and fixed, the exhaust pipe is connected in series with the buffer kettle and the vacuum pump, the glue inlet is locked, and the vacuum pump is turned on for vacuuming. When the vacuum pump pressure reaches one atmosphere, check whether there is any leakage. After confirming that the whole device is leak-proof, the glue inlet pipe is connected to a beaker, and the beaker contains degassed epoxy resin glue. Then the glue inlet is opened, and the epoxy resin glue enters the sealed mold cavity under the action of the vacuum pump. After the epoxy resin glue completely infiltrates the fiber braid, the glue inlet and the exhaust port are sealed, and the mixture is cured at room temperature for 24 hours, and then placed in an oven and post-cured at 60°C for 2 hours. After taking it out, the hybrid composite material is removed from the mold, and the demoulding cloth, the guide net, and the vacuum bag are removed to obtain a carbon-glass super-hybrid composite material.

8. The method for preparing the high-toughness carbon-glass super-hybrid composite material according to claim 6, characterized in that: The preparation method of epoxy resin glue is as follows: mix epoxy resin and curing agent in a mass ratio of 3:1 and stir evenly. The mixed epoxy resin contains a large number of bubbles. At this time, the epoxy resin needs to be placed in a vacuum drying oven to vent for 10-12 minutes. After venting, the epoxy resin is transparent, clear and uniform inside without bubbles.

9. A high-toughness carbon-glass super-hybrid composite material prepared according to the preparation method described in any one of claims 1 to 8.

10. Application of the high-toughness carbon-glass super-hybrid composite material according to claim 9 on the inner panel frame of an automobile door, characterized in that: The elongation at break of the high-toughness carbon-glass superhybrid composite is 1.9%, the ultimate bending strain is 2.66%, the loss factor is 0.595, the damage area after impact test is 4.2%, and the absorbed energy is 24.8 J.

Citation Information

Patent Citations

  • An airflow disturbance type carbon fiber spreading device

    CN114197098B

  • Hybrid carbon fiber spun yarn and hybrid carbon fiber spun yarn fabric using same

    CN101124355A

  • Automobile battery box made of multi-axial hybrid fiber composite material and manufacturing method of automobile battery box

    CN106626433A

  • Hybrid reinforcement assemblies

    CN106794638A

  • Method for manufacturing main beam and auxiliary beam of wind power blade by mixing carbon fiber pultruded sectional material and glass fiber textile

    CN108312575A

Cited By

  • Production method and application of high-modulus glass fiber fabric

    CN119974288A